Training on Use of ANACIM Senegal ENACTS Platform and Maprooms - Trzaska, Sylwia; Hansen, James; Diop, Lamine; Sal, Ndaye Amy; Mbengue, Asse; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In order to support a wider use of the platform, ANACIM in collaboration with the IRI conducted a workshop to introduce agricultural professionals to the data and tools that are available through ANACIM’s ENACTS platform and Maprooms, and train them to access, interpret and apply these tools. The training covered basic climate concepts, the ENACTS approach, demonstration and hands-on experience using ANACIM’s data analysis Maproom tools, and discussion of how these analyses can address a range of climate-related problems and climate-sensitive management decisions. Participants were introduced to a new seasonal rainfall forecast Maproom that was designed to increase the usefulness of probabilistic seasonal climate forecasts for local decision making for agriculture and other climate-sensitive sectors.